Knowledge on Risk Factors of Coronary Heart Disease among Middle Aged Administrative Staffs of Kathmandu - Shrestha, Soni; Gautam, Deepa (Journal of Advanced Academic Research, 2017)
Background: Progressive urbanization and adoption of the “western” lifestyle contributes to the rising burden of cardiovascular diseases in the developing world. Coronary Heart Disease (CHD) is no longer confined by geographical area or socioeconomic boundary. Knowledge is an important pre-requisite for implementing both primary and secondary preventive strategies of CHD and for behavioral change. Objective: This study attempts to quantify level of knowledge on risk factors of Coronary Heart Disease among middle aged administrative staffs of Tribhuvan University, Kritipur Kathmandu.Methodology: Descriptive Cross Sectional  study was conducted in different departments of Tribhuvan University, Kathmandu from December 22, 2014 to January 2, 2015.A total of 130 middle aged administrative staffs (40-60 years) have participated in the study. Structured questionnaires and interview schedule were used to collect data and descriptive statistics was used for data analysis. Results: Among total respondents, 56.2 % had mean knowledge score equal to or more than 13.91. Only less than half (47.7%) knew age as non - modifiable risk factor of CHD followed by sex (30.8%) and family history (30%). Regarding modifiable risk factors, most participant response was fatty food consumption (80.8%) followed by tobacco use (80%), excessive alcohol consumption (78.5%), hypertension(76.2%), Stress(74.6%), lack of exercise/inactive lifestyle (73.8%), mellitus (46.9%). In regards to the symptom of CHD, most cited response was chest Obesity (70.8%), excessive salt consumption in diet (60.8%) and diabetes pain/discomfort (55%). The risk factors prevalent among the study participants included overweight (44.6%) and alcohol consumption (30.8%)Conclusion: The findings concluded that significant percentage (43.8%) of respondent’s mean knowledge score was less than 13.91. Thus, understanding of the behavioral determinants of heart disease knowledge and risk factors is necessary in designing effective prevention strategies.  Journal of Advanced Academic Research Vol. 3, No. 2, 2016, page : 1-13